Strategi Social Media Marketing USS Feed Dalam Membangun Social Media Engagement - Darma Tri Putra; Jamiati KN (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The creative industry is changing the way people communicate from physical contact to using internet technology. A strategy that utilizes social media as a means of growing social media engagement. The aim of this research is to explain USS Feed's social media marketing strategy in building social media engagement. This research uses a qualitative approach, with descriptive methods and to obtain research data using observation, documentation and in-depth interviews. Next, it is analyzed by reducing the data, presenting the data, and making a summary by drawing conclusions. The theory used. Social media strategy, namely business goals: building a company image, target audience: millennial generation and gen-z, social analysis gathering information that is developing among gen-z and millennials, planning and brainstorming big ideas about things that are currently happening to create a content, human integrity advertising and social media: promotional strategies on other social media platforms, platform implementation: designing the flow and content of content so that it provides appeal. The theory of social media engagement is: the content resonates with them, originates from a source the trust, reflects something about themselves, other responds, you respond, you give benefits. Research shows that the strategy implemented by USS Feed has accommodated all elements of social media marketing and social media engagement strategies well so that it can increase social media engagement.